Spin injection and detection in In0.53Ga0.47As nanomembrane channels transferred onto Si substrates - Yang, Yun-Suk; Um, Doo-Seung; Lee, Youngsu; Shin, JaeKyun; Chang, Joonyeon; Koo, Hyun Cheol; Ko, Hyunhyub; Kim, Hyung-jun (IOP PUBLISHING LTD, 2014)
We investigate the electrical spin injection and detection in In0.53Ga0.47As nanomembranes, which are originally. grown on InP substrates and subsequently heterogeneously integrated on SiO2/Si substrates via a transfer printing technique. Through local and nonlocal spin valve measurements employing the In0.53Ga0.47As nanomembrane channels on SiO2/Si substrates, we successfully observe the electrical detection of spin injection from Ni81Fe19 ferromagnetic metal electrodes into the channels. Furthermore, nonlocal spin valve signals are detected up to T = 300 K without mixing with anisotropic magnetoresistance, which is evidently verified by observing a memory effect. (C) 2014 The Japan Society of Applied Physics
Keywords: QUANTUM-WELLS; SEMICONDUCTOR; SILICON; ACCUMULATION; TRANSISTORS; PRECESSION; TRANSPORT; LAYERS